The 2018 Revision of Italian Dietary Guidelines: Development Process, Novelties, Main Recommendations, and Policy Implications - Rossi, Laura; Berni Canani, Sibilla; Censi, Laura; Gennaro, Laura; Leclercq, Catherine; Scognamiglio, Umberto; Sette, Stefania; Ghiselli, Andrea (Frontiers in Nutrition, 2022)
The fourth edition of the Italian Dietary Guidelines (IDGs) for Healthy Eating was published in 2019. The objective of this paper is to describe the developmental process of IDGs, the main recommendations, the differences with previous revisions, and the concordance and differences with international guidance on a healthy diet. A National Commission oversaw IDG development. A Scientific Dossier (SD), including analysis on nutrition, health, and risk factors status in Italy, was the reference for IDGs preparation. The IDGs are based on the principles of the Mediterranean Diet and are mainly aimed to prevent obesity and nutrition-related non-communicable diseases. The IDGs included 13 directives that were divided into four conceptual blocks: i) how to balance weight; ii) foods to be promoted; iii) foods to be limited; and iv) how to ensure a varied and sustainable diet. Each directive has a box summarizing the key recommendation, myths lists, and false beliefs to be dispelled. The topics of sustainability and the correct approach to food supplementation and weight-loss diet were introduced in the present edition of IDGs. This paper contributes to the debate on the complexity of derivation of Dietary Guidelines and their adaptation to the national context.